2013
DOI: 10.4314/ahs.v13i3.15
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity in stroke patients attending a neurology clinic in Nigeria

Abstract: Back ground: Stroke produces a wide range of mental and emotional disorders. Neuropsychiatric complications associated with stroke may have negative effects on the social functioning, overall quality of life and the recovery of motor functioning of stroke survivors. Objective: To determine the prevalence and nature of psychiatric morbidity among stroke patients attending neurology outpatient clinic of the University of Ilorin Teaching Hospital (UITH), Ilorin-Nigeria. Methods: All patients with stroke aged 18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…While most relied on a variety of rating scales, clinical interview and formal diagnostic criteria were used in five studies [ 16 , 24 , 26 , 28 , 30 ]. Only one of these studies [ 30 ] used the criteria in the 10th revision of the International Classification of Diseases (ICD-10) [ 31 ]. The other studies using clinical diagnostic criteria relied on the Diagnostic and Statistical Manual of Mental Disorders [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While most relied on a variety of rating scales, clinical interview and formal diagnostic criteria were used in five studies [ 16 , 24 , 26 , 28 , 30 ]. Only one of these studies [ 30 ] used the criteria in the 10th revision of the International Classification of Diseases (ICD-10) [ 31 ]. The other studies using clinical diagnostic criteria relied on the Diagnostic and Statistical Manual of Mental Disorders [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, only one study [ 17 ] included participants recruited from their homes, rather than in hospital or physical rehabilitation settings. The remaining eight studies were conducted among medical inpatients [ 20 22 ] or outpatients [ 3 , 25 , 27 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier reviews showed PSD to be the commonest mental disorder in survivors, with up to 25.5% prevalence rate reported in previous local studies. 10 , 11 , 12 Additionally, studies have shown significant associations between emotional disorders like depression and poorer quality of life (QoL) in stroke survivors. 13 , 14 Such comorbidity of stroke with depression has been described as the ‘double burden’ of stroke because both depression and stroke are leading contributors to total years lost to disability based on the global burden of diseases report.…”
Section: Introductionmentioning
confidence: 99%